Complementarities and organizational (Mis)fit: A retrospective analysis of the Toyota recall crisis - Arnaldo Camuffo; Miriam Wilhelm (Journal of Organization Design, 2016)
During the past six decades, the Toyota Motor Company established a 'lean' production and management system (the Toyota Way), which has become an iconic template for a high performing and learning organization. The massive recall crisis of 2009/2010 distorted Toyota's image of a role model for a lean organization heavily. This case study analyzes retrospectively how the carmaker deviated from their original organizational configuration that was distinctive for its lean management system. We illustrate how managerial decisions geared towards extensive growth and globalization distorted complementarities among central elements of the Toyota Way, and ultimately caused organizational misfit. Whereas most of the literature on complementarities and organizational fit has emphasized processes of adaptation and evolution toward internal fit or misfit that are triggered by exogenous environmental changes, our case study of Toyota shows that external misfit can also be the unintended consequence of deliberate changes in the firm's system of interdependent choices.
Keywords: 650; Toyota; Lean production; Organizational complementarities; External and internal misfit